Answer: 26
Step-by-step explanation:
First Data: (4 - 7)^2
Second data: (6 - 7)^2
Third Data: (11 - 7)^2
So the SST is (4 - 7)^2 + (6- 7)^2 + (11 - 7)^2 = 9 + 1 + 16 = 26
Hope this helps! :)
Answer:
372.233
heart if it helped brain if im cool
<span>Simplifying
x + -1.4 = 7.82
Reorder the terms:
-1.4 + x = 7.82
Solving
-1.4 + x = 7.82
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '1.4' to each side of the equation.
-1.4 + 1.4 + x = 7.82 + 1.4
Combine like terms: -1.4 + 1.4 = 0.0
0.0 + x = 7.82 + 1.4
x = 7.82 + 1.4
Combine like terms: 7.82 + 1.4 = 9.22
x = 9.22
Simplifying
x = 9.22</span>
5+4❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤❤